Chemical Constituents, Antioxidative and Antimicrobial Activities of Essential Oil and Oleoresin of Tailed Pepper (Piper Cubeba L) - Singh, Gurdip (2007)
The antimicrobial and antioxidant potentials of hydrodistilled essential oil and oleoresin (obtained using acetone as a solvent) of tailed pepper were carried out by different techniques. The results obtained from antioxidant activity measurements of essential oil and oleoresin against mustard oil were measured for duration of 28 days in terms of peroxide, thiobarbituric acid, total carbonyl and p-anisidine values. The results obtained from butylated hydroxyanisole (BHA) and butylated hydroxytoluene (BHT) was similar to both the oleoresin and essential oil. In addition, the inhibitory action in linoleic acid system was studied by monitoring accumulation of peroxide concentration. The radical scavenging capacity of both essential oil and oleoresin on 2, 2'-diphenyl-1-picrylhydrazyl (DPPH) radical were (71.2%) and (69.77%) respectively at 25 µL/mL. It was relatively lower in comparison with synthetic antioxidants (BHA-96.41%; BHT- 95.91%). The results obtained from reducing power, chelating effect and hydroxyl radical scavenging effect was also supported the antioxidant of essential oil and oleoresin. The tailed pepper essential oil and oleoresin showed 100% mycelial zone inhibition against Penicillium viridicatum at 3000 and 2000 ppm respectively in the poison food method. It is interesting to note that the essential oil revealed 100% clear zone inhibition against Aspergillus flavus at all tested concentrations. The chemical characterization of tailed pepper essential oil by GC and GC-MS resulted in the identification of 44 components accounting for 97.8% of the oil.